Beauty is What Space Literally Creates - Hamidi, Nabil (My University, 2025)
This article advances the claim that beauty is not an autonomous property of objects or minds but a phenomenon that arises from space itself. The argument is established through three empirically grounded criteria: temporal precedence, ontological asymmetry, and necessary-condition reasoning. First, contemporary science confirms that space existed long before any aesthetic forms or perceiving agents emerged. Second, beauty cannot manifest in the absence of space, whereas space demonstrably existed without any aesthetic expression. Third, there is no scientific account in which beauty precedes the formation of space-time. Because space temporally precedes beauty, because beauty relies on space to occur, and because space is independent of beauty, the conclusion follows: beauty is literally and physically generated by space.